ANALYSIS OF LEADERSHIP STYLES IN IMPROVING THE PERFORMANCE OF STATE CIVIL APPARATUS AT THE REGIONAL FINANCIAL AND ASSET MANAGEMENT AGENCY OF SUPIORI REGENCY - Alfred Sawor, Roberth; Amiruddin, Amiruddin; Djunaedi, Djunaedi (Gema Kampus IISIP YAPIS Biak, 2025)
This research analyzes leadership style in improving the performance of Civil Service Apparatus (ASN) at the Regional Financial and Asset Management Body (BPKAD) of Supiori Regency. Using qualitative descriptive methodology with interview and observation techniques, the study involved five informants representing key leadership positions at BPKAD. Research findings reveal that the leadership style applied at BPKAD Supiori demonstrates adequate effectiveness in improving employee performance, with indicators including decision-making capability, employee motivation, communication, control of subordinates, and emotional control. The study identified six influential factors: leader personality, competence and skills, relationships with subordinates, motivation and organizational objectives, external environmental influence, and adaptation capability. However, the research also found deficiencies in communication effectiveness that require improvement to minimize miscommunication-related errors. The findings indicate that effective leadership style significantly influences employee work motivation and performance optimization in fulfilling service duties. This research contributes to understanding how leadership approaches impact organizational performance in government bodies and provides recommendations for strengthening communication and adaptive leadership strategies to achieve optimal service delivery and employee performance